Introduction to the sun and stars - Green, Simon F.; Jones, Mark H. (Cambridge, Cambridge University Press, 2003)
Compiled by a team of experts, this textbook has been designed for elementary university courses in astronomy and astrophysics. It starts with a detailed discussion of our nearest star, the Sun, and describes how solar physicists have come to understand its internal workings. It then considers how astronomers go about studying the basic physical properties and life-cycles of more distant stars, and culminates with a discussion of the formation of exotic objects such as neutron stars and black holes. Written in an accessible style that avoids complex mathematics, and illustrated in colour throughout, this book is suitable for self-study and will appeal to amateur astronomers as well as undergraduate students. It contains numerous helpful learning features such as boxed summaries, student exercises with full solutions, and a glossary of terms. The book is also supported by a website hosting further teaching materials.
Appendix A1-A5, 328-334p; Glossary 345-358p; Index 366-373p.
Keywords: Sun; Stars; Physics